2015
DOI: 10.1165/rcmb.2014-0269tr
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis and Ionic Mechanisms in Pulmonary Fibroblasts

Abstract: Fibroblasts are key cellular mediators of many chronic interstitial lung diseases, including idiopathic pulmonary fibrosis, scleroderma, sarcoidosis, drug-induced interstitial lung disease, and interstitial lung disease in connective tissue disease. A great deal of effort has been expended to understand the signaling mechanisms underlying the various cellular functions of fibroblasts. Recently, it has been shown that Ca(2+) oscillations play a central role in the regulation of gene expression in human pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 141 publications
2
53
0
Order By: Relevance
“…Although the in vivo TGFβ1 level was not affected by the loss of TRPV4 in healing corneas, the decline in myofibroblast transdifferentiation may be due to impaired cognate receptor function or signal transduction coupling inducing transactivation of other Ca 2+ influx pathways besides TRPV4. This is possible since there are numerous other Ca 2+ influx pathways besides TRPV4 which can be activated to induce increases in Ca 2+ influx [30]. The possible involvement of different Ca 2+ influx pathways besides TRPV4 may be a factor contributing to the variable effects of TGFβ receptor activation inducing responses accompanying transdifferentiation of fibroblasts into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo TGFβ1 level was not affected by the loss of TRPV4 in healing corneas, the decline in myofibroblast transdifferentiation may be due to impaired cognate receptor function or signal transduction coupling inducing transactivation of other Ca 2+ influx pathways besides TRPV4. This is possible since there are numerous other Ca 2+ influx pathways besides TRPV4 which can be activated to induce increases in Ca 2+ influx [30]. The possible involvement of different Ca 2+ influx pathways besides TRPV4 may be a factor contributing to the variable effects of TGFβ receptor activation inducing responses accompanying transdifferentiation of fibroblasts into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no therapeutic strategy targets [Ca 2+ ] i signaling in fibroblast-mediated pulmonary diseases [48], but our results suggest potential means of controlling fibrotic pulmonary diseases by manipulating [Ca 2+ ] i signaling events. In particular, we suggest antioxidant, [Ca 2+ ] i signaling pathway inhibitor, and TRPM2 inhibitor treatments should be considered for therapeutic trials in fibrotic diseases.…”
Section: Discussionmentioning
confidence: 86%
“…Intracellular calcium is critical for regulating various functions of fibroblasts, including cell proliferation, matrix remodelling and myofibroblast transdifferentiation . Cytoplasmic calcium oscillations activate extracellular signal‐regulated kinase (ERK) and enhance fibroblast survival and interstitial fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium is critical for regulating various functions of fibroblasts, including cell proliferation, matrix remodelling and myofibroblast transdifferentiation. 25 Cytoplasmic calcium oscillations activate extracellular signal-regulated kinase (ERK) and enhance fibroblast survival and interstitial fibrosis. 26 In this study, we found that Pitx2cknockdown cells exhibited greater cytoplasmic calcium concentrations compared to control cells in both the baseline calcium-free solution and the 2 mmol/L calcium-containing solution.…”
Section: Discussionmentioning
confidence: 99%